2020
DOI: 10.3390/w12071913
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Optimal Sites for a Rainwater-Harvesting Agricultural Scheme in Iran Using the Best-Worst Method and Fuzzy Logic in a GIS-Based Decision Support System

Abstract: Rainwater-harvesting (RWH) agriculture has been accepted as an effective approach to easing the overexploitation of groundwater and the associated socioeconomic impacts in arid and semiarid areas. However, the stability and reliability of the traditional methods for selecting optimal sites for RWH agriculture need to be further enhanced. Based on a case study in Tehran Province, Iran, this study proposed a new decision support system (DSS) that incorporates the Best-Worst Method (BWM) and Fuzzy logic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
0
17
1
1
Order By: Relevance
“…Modelagem fuzzy para identificar áreas sensíveis a erosão do solo pelo vento usando dados de informações geográficas, sensoriamento remoto nas porções áridas e semiáridas na Sérvia. (Aghaloo & Chiu, 2020) Identifying optimal sites for a rainwater-harvesting agricultural scheme in iran using the best-worst method and fuzzy logic in a GISbased decision support system É proposto um sistema de suporte a decisão geográfica utilizando BWM e logica fuzzy para tornar sustentável a agricultura dependente da água da chuva no ambiente árido e semiárido no Iran. (Coulon-Leroy et al, 2013) Imperfect knowledge and data-based approach to model a complex agronomic feature -Application to vine vigor…”
Section: Identifying Areas Sensitive To Wind Erosion-a Case Study Of ...unclassified
“…Modelagem fuzzy para identificar áreas sensíveis a erosão do solo pelo vento usando dados de informações geográficas, sensoriamento remoto nas porções áridas e semiáridas na Sérvia. (Aghaloo & Chiu, 2020) Identifying optimal sites for a rainwater-harvesting agricultural scheme in iran using the best-worst method and fuzzy logic in a GISbased decision support system É proposto um sistema de suporte a decisão geográfica utilizando BWM e logica fuzzy para tornar sustentável a agricultura dependente da água da chuva no ambiente árido e semiárido no Iran. (Coulon-Leroy et al, 2013) Imperfect knowledge and data-based approach to model a complex agronomic feature -Application to vine vigor…”
Section: Identifying Areas Sensitive To Wind Erosion-a Case Study Of ...unclassified
“…Furthermore, location analysis for the proposed new WWTPs and water-reuse plants can be identified by using the best-worst method in a GIS-based Decision Support System (DSS). This method was used, for instance, to identify optimal sites for a rainwater-harvesting agriculture scheme in Iran to ease the overexploitation of groundwater [39].…”
Section: Land-use and Water Requirementsmentioning
confidence: 99%
“…The outcomes demonstrated that the data produced using the BWM were reliable and consistent [25]. (e) Choosing the best sites for rainwater-harvesting agriculture in arid and semiarid regions, using GIS data and rainfall patterns [26]. (f) Evaluating the Grey mangrove reforestation process reported for the first time in the Persian Gulf.…”
mentioning
confidence: 92%